Unemployment benefits or taxes: How should policy makers redistribute income over the business cycle? - Susanne Ek (Uppsala University, Department of Economics, 2012)
This paper studies optimal unemployment benefit levels and optimal proportional income tax rates over the business cycle. Previous research suggests that policy makers should make unemployment insurance (UI) dependent on the business cycle because the UI system can be used to smooth consumption across different economic states. However, high benefits increase unemployment. An alternative way to redistribute income is to vary tax rates over the business cycle. In this paper, we develop an equilibrium search and matching model with risk-averse workers and two states, namely, a good and a bad state.The model yields potential ambiguity concerning the welfare effects of business cycle-dependent UI. The model is calibrated to United States (U.S.) labor market data. The numerical results suggest that higher benefits in the bad state are optimal, but the benefit differential is small. A more efficient way for policy makers to redistribute income over the business cycle is to decrease taxes in the bad state. Compared to an optimal uniform system, however, differentiation yields small welfare gains. Nevertheless, imposing two tax rates strictly dominates imposing two benefit levels. This finding is robust to a wide range of sensitivity checks.
urn:nbn:se:uu:diva-168210
Keywords: E32; H24; J64; J65; 330; job search; business cycles; unemployment insurance; time-varying benefits and taxes; Arbeitsplatzsuchmodell; Arbeitslosenversicherung; Einkommensteuertarif; Konjunktur; Einkommensumverteilung; Theorie; USA